THE CROP-LIVESTOCK INTEGRATION INNOVATION USING PALM OIL BY-PRODUCTS TECHNOLOGY TO SUPPORT BEEF CATTLE PRODUCTION IN WEST SUMATRA - Yolas Pendra, Edy Mawardi and Asmak, Abdullah M Bamualim, Fuad Madarisa, (International Journal of Agricultural Sciences, 2015)
A study has been conducted on the crop-livestock integration innovation using palm oil by-products technology to support beef cattle production in 2014. The collected data consisted of (i) Socio-economic aspects, (ii) The body weight gain of cattle, and (iii) Palm oil production. These data were taken from Sri Langgeng farmers group (13 respondents) in Dharmasraya district and Tanjung Keramat farmers group (10 respondents) in West Pasaman district. The results of the socio economic aspects showed; the Â average age of farmers was 39 years old, owned palm oil plantation of 2,2 and, 4,1 ha, and owned of 4.2 and 6.2 head of cattle in Tanjung Keramat and Sri Langgeng respectively. The average monthly income was Rp 1.63 million and about Rp 1.05 million derived from livestock contribution in Tanjung Keramat, and Rp 1.65 million and about Rp 1.71 million derived from livestock contribution in Sri Langgeng. Feeding a supplement of palm oil by-products increased cattle growth by about 0.14 and 0.09 kg/head/day at Sri Langgeng and Tanjung Keramat respectively. In contrast, the animals in a control treatment experienced body weight losses of -0.17 and -0.11 kg/head/day. The application of organic fertilizer from cattle manure, above the inorganic fertilizer, increased the palm oil fruit by 39.4% and 48.4%. The research proved that there is an opportunity to accelerate the adoption process of crop-livestock integration in palm oil plantation areas in West Sumatra.